Community Dynamics and Policy Resistance as Determinants of Green Transition Adoption: A Cross-Sectional Study in Indonesian Cities - Dwi Valinia Ivanka; Rheina Weisch Fedre; Sarah Armalia (Open Access Indonesia Journal of Social Sciences, 2026)
Rapid urbanization in Southeast Asian cities has intensified environmental pressures, yet the adoption of green transition practices remains uneven across communities. While individual-level determinants have been extensively studied, the contributions of community-level social factors remain poorly understood in developing urban contexts. This cross-sectional study examined determinants of green transition adoption (GTA) among 398 residents of four Indonesian cities—Surabaya, Semarang, Bandung, and Yogyakarta—between March and August 2024. Binary logistic regression with nine predictors revealed that Community Dynamics was the strongest predictor (AOR=2.87, 95% CI: 1.79–4.60, p<0.001), followed by Policy Resistance (AOR=2.18, 95% CI: 1.39–3.42, p<0.001) and Social Equity Perception (AOR=1.92, 95% CI: 1.23–3.00, p=0.004). Environmental Knowledge Score and Health Risk Perception were not significant in the multivariate model. The model demonstrated adequate discrimination (AUC=0.79) and calibration (Hosmer-Lemeshow p=0.548), explaining 32.6% of outcome variance. Mediation analysis revealed that 35% of the CD–GTA relationship operated through social equity perception (Sobel z=3.21, p=0.001). Community-level social cohesion and institutional legitimacy are more powerful drivers of green transition adoption than individual knowledge or risk perception.